(untitled) (Journal of Information Technologies in Education (ITE), 2014)
The article covers the main aspects of the implementation and application of information technology in preparing future elementary school teachers, which reveals the need for change in content, forms and methods in the practice of primary school. The analysis of the creation of computer-based environment of elementary school provided a basis to determine the theoretical and methodological foundations of information technology training students in high school.